Evaluation of fungicides for the control of bean rust (Uromyces appendiculatus). - González, Miguel; García, Evelio (Agronomía Mesoamericana, 2016)
Five trials using a randomized complete block design with four replicates were performed to determine the effectiveness of several fungicide treatments against the bean rust as well as their effect on yields. The chemicals screened were bitertanol, diclobutrazol, diniconazole, hexaconazole, iprodione, metiram, oxycarboxin, penconazole, pyracarbolid, triadimefon, triadimenol and tridemorph + maneb which were compared with sulphur, used as standard and with an untreated check plot. The best results were obtained with Bitertanol 30 EC, Hexaconazole 5 SC and Oxycarboxin 75 WP sprayed at 0.5 kg/ha on a 14 days interval. No significative differences were found among the treatments, which statistically excelled Sulphur 80 WP sprayed weekly at 3 kg/ha and raised the yields significantly inrelation with it.